Valorization of Urban Street Tree Pruning Residues in Biorefineries by Steam Refining: Conversion Into Fibers, Emulsifiers, and Biogas - Hagel, Sebastian; Lüssenhop, Phillipp; Walk, Steffen; Kirjoranta, Satu; Ritter, Annalena; Bastidas Jurado, Carla Gabriela; Mikkonen, Kirsi S.; Tenkanen, Maija; Körner, Ina; Saake, Bodo (Frontiers in Chemistry, 2021)
Street tree pruning residues are a widely available and currently under-valorized bioresource. Their utilization could help alleviate an increasing biomass shortage and offset costs of the pruning process for the municipalities. In this work, a holistic valorization pathway of pruning residues leading to fibers, oligosaccharides, biogas and compost is presented. For this, representative mixtures of tree pruning materials from the most prevalent street tree genera (Oak, Linden, Maple) found in Hamburg (Germany) were prepared by shredding and cleaning procedures. Collection of sample material was performed in summer and winter to account for seasonality. A steam-based fractionation was conducted using treatment severities ranging from log R0 = 2.5 to 4.0. At the highest severity, a fiber yield of around 66% and liquor yield of 26 to 30% was determined. The fibers were evaluated in respect to their properties for paper product applications, with higher treatment severities leading to higher paper strengths. From the oligosaccharide-rich liquor emulsions were created, which showed promising stability properties over 8 weeks of storage. The liquors and the rejects from the material preparation also displayed good potential for biomethane production. Overall, the differences between material collected in summer and winter were found to be small, indicating the possilibity for a year-round utilization of pruning residues. For the presented utilization pathway, high severity treatments were the most promising, featuring a high liquor yield, good biomethane potential and the highest paper strengths.